Laser-Assisted Synthesis, Reduction and Micro-Patterning of Graphene: Recent Progress and Applications - Singh, D (Elsevier B.V., 2017)
Laser-based approaches for graphene synthesis, reduction, modification, cutting and micro-patterning have been developed and applied to the fabrication of various electronic devices. These laser-based techniques exhibit several advantages over alternative methods: low temperature, shorter reaction times, environmentally friendly, energy saving, catalyst free growth on insulating substrates, high productivity, better reproducibility, scalability, excellent control over experimental parameters. Given the importance of the subject, in the last few years a remarkable increase in the number of scientific articles has occurred in this area. Direct fabrication of graphene patterns for micro-supercapacitors, flexible electrodes, field-effect-transistors, and sensors are some of the examples. Direct laser writing enables local graphene synthesis and fabrication of graphene patterns on graphene oxide films. It can be used to achieve band gap modulation, removal of surface functionalities, conductivity enhancement, exfoliation and porous structure formation. The aim of this review is to collect some of the most relevant research efforts published on this important topic, with emphasis in the articles published in the last few years. After an introduction highlighting the main factors affecting the outcome of laser-materials interactions, devices built using direct laser writing (DLW) on graphene oxide/graphene films and the experimental conditions used for their fabrication are summarized. Some of the expected directions for promising future research in this area are briefly discussed. © 2017 Elsevier B.V.